Comparative Genomics and Biosynthetic Potential Analysis of Two Lichen-Isolated Amycolatopsis Strains - Sánchez-Hidalgo, Marina; González, Ignacio; Díaz-Muñoz, Cristian; Martínez, Germán; Genilloud, Olga (Frontiers in Microbiology, 2018)
Actinomycetes have been extensively exploited as one of the most prolific secondary metabolite-producer sources and continue to be in the focus of interest in the continued search of novel bioactive compounds. The availability of less expensive next generation genome sequencing techniques has not only confirmed the extraordinary richness and broad distribution of silent natural product biosynthetic gene clusters (BGCs) among these bacterial genomes, but also has allowed he incorporation of genomics in bacterial taxonomy and systematics. As part of our efforts to isolate novel strains from unique environments, we explored lichen-associated microbial communities as unique assemblages to be studied as potential sources of novel bioactive natural products with application in biotechnology and drug discovery. In this work, we have studied the whole genome sequence of two new Amycolatopsis strains (CA-126428 and CA-128772) isolated from tropical lichens and performed a comparative genomic analysis with 41 Amycolatopsis publicly available genomes. This work has not only permitted to infer and discuss their taxonomic position on the basis of the different phylogenetic approaches used, but has allowed to assess the richness and uniqueness of the biosynthetic pathways associated to primary and secondary metabolism, and to provide a first insight on the potential role of these in the lichen associated bacteria in the microbial community.